Frequency and characteristics of the V617F mutation in 23 cerebral venous sinus thrombosis patients with thrombocytosis - Qiang Ma (Journal of International Medical Research, 2020)
Objective To analyse the frequency and characteristics of the Janus kinase 2 ( JAK2) V617F mutation in patients with cerebral venous sinus thrombosis (CVST) with thrombocytosis. Methods The study enrolled CVST patients with thrombocytosis that had undergone JAK2 V617F mutation detection to determine the frequency of the JAK2 V617F mutation in this cohort. Correlations between patient demographics, whole blood cell counts, targeted sequencing results and JAK2 V617F mutation status were determined. Results A total of 23 patients were enrolled in the study: 11 (47.8%) with the JAK2 V617F mutation and 12 (52.2%) without the JAK2 V617F mutation. The mean platelet count was significantly higher in patients with the JAK2 V617F mutation than in patients without the mutation (478.1 ± 107.4 × 10 9 /l versus 374.4 ± 54.1 × 10 9 /l, respectively). There were no significant differences in age, sex, white blood cell count or haemoglobin level between the two groups. Other than single nucleotide polymorphisms, no hot-spot mutations associated with myeloid tumours other than the JAK2 V617F mutation were detected in four CVST patients that underwent targeted sequencing. Conclusion The JAK2 V617F mutation was frequently detected in CVST patients with thrombocytosis and it was associated with higher platelet counts.